Guidelines for New Normal Restaurant Design to Establish Standards for Enhancing Hygiene in Restaurants Amid the COVID-19 Pandemic (2021–2022): A Case Study of Restaurants in Bangkok and Nonthaburi Provinces - Sawangmake, Saranyoo (Rajamangala University of Technology Tawan-ok Social Science Journal, 2025)
This research had two main objectives (1) to examine the impact of the COVID-19 pandemic on lifestyle behaviors under the New Normal, particularly in relation to urban and community-based restaurants, and (2) to develop restaurant design guidelines that align with public health and safety measures during a pandemic. The study focused particularly on “khao gaeng” (curry over rice) restaurants in Bangkok and Nonthaburi, which remained popular even during the pandemic. Data collection involved both qualitative and quantitative methods from 120 restaurants, 300 general consumers, and 340 specific users of khao gaeng restaurants, along with 15 key informants. The findings revealed that consumers preferred open-air restaurants, spent less time dining in, prioritized hygiene, and still mostly used cash for transactions. The analysis led to the development of six key recommendations for improving restaurant spaces. (1) Designating open, well-ventilated zones (2) Laying out restaurant floor plans with physical distancing, clear circulation paths, and minimized shared touchpoints (3) Enhancing ventilation systems with options like HEPA filters and open windows (4) Reducing contact through QR code menus and online payments (5) Creating one-way circulation and less comfortable seating to shorten dining duration and (6) Using lighting that reduces privacy and subtly encourages shorter stays. These strategies can be practically implemented in small- and medium-sized restaurants with minimal investment and are considered concrete solutions that can boost consumer confidence and promote long-term public health.